2012
DOI: 10.1128/iai.00425-12
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma gondii Peptide AS15 Elicits CD4 T Cells That Can Control Parasite Burden

Abstract: ABSTRACTThe apicomplexan parasiteToxoplasma gondiican cause severe disease in immunocompromised individuals. Previous studies in mice have focused largely on CD8+T cells, and the role of CD4 T cells is relatively unexplored. Here, we show that immunization of the C57BL/6 strain of mice, in which the immunodominant CD8 T cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…We used MHCI tetramers that bind CD8 + T lymphocytes specific for the endogenous T. gondii epitope Tgd057 and MHCII tetramers that bind CD4 + T cells specific for the Toxoplasma epitope CD4Ag28m (35, 36). The frequency of parasite-specific CD4 + and CD8 + T cells was equivalent in Ex3 DC−/− and Ex3 fl/fl mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used MHCI tetramers that bind CD8 + T lymphocytes specific for the endogenous T. gondii epitope Tgd057 and MHCII tetramers that bind CD4 + T cells specific for the Toxoplasma epitope CD4Ag28m (35, 36). The frequency of parasite-specific CD4 + and CD8 + T cells was equivalent in Ex3 DC−/− and Ex3 fl/fl mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Grover et al (2012) reported decreased parasite load in vaccinated mice due to increased level of CD4? T-lymphocytes in response to vaccination by single parasite peptide (AS15), which is one of the constituent of ESA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to H-2 d mice, in which the CD8 T cell response dominates over the CD4 T cell response (Blanchard et al, 2008), B6 mice generated a robust CD4 T cell response but a weaker CD8 response towards T. gondii (Figure 1A, top panels; (Grover et al, 2012). To selectively expand the CD8 T cells, we used MHC Class II deficient dendritic cells as APCs for in vitro restimulations.…”
Section: Resultsmentioning
confidence: 97%
“…with 1-5×10 6 irradiated tachyzoites of the Type II Prugniuad-tomato-OVA strain (Pru) as described (Grover et al, 2012). For inducing protection, mice were immunized in the footpad with activated B6 bone-marrow derived dendritic cells (BMDCs) loaded with synthetic peptide as described (Blanchard et al, 2008).…”
Section: Methodsmentioning
confidence: 99%